Jüngers kødgryder - Schlosser, Jan T. (Academic Quarter | Akademisk kvarter, 2010)
Jan T. Schlosser Jüngers kødgryder (Jüngers’ fleshpots). The article analyses Ernst Jüngers use of the decay of flesh and mistreatment as critique of civilization. The focus in the article is on Der Kampf als inneres Erlebnis (1922) and Das Abenteuerliche Herz (1929), and it is demonstrated how Jüngers as a trademark stresses the dark underbelly of modernity through the use of decaying flesh in a way that can be compared with Edgar Allan Poe and Marquis de Sade. This takes Jüngers away from the enlightenment tradition and towards a more intuitive perception of civilization.